Principal Leadership Management to Enhance Collaborative Culture at SD Negeri 2 Garunglor - Pujiyanto Pujiyanto; Didi Supriadi; Welius Purbonuswanto (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to analyze the role of principal leadership management in enhancing the collaborative culture at SD Negeri 2 Garunglor. A qualitative case study approach was employed to explore leadership practices and their influence on teacher collaboration within the school environment. Data were collected through interviews, observations, and document analysis involving the principal, teachers, and relevant stakeholders. The findings reveal that the principal plays a significant role in fostering a collaborative culture through the implementation of a shared vision, participative decision-making, effective communication, professional support, and transformational leadership practices. These leadership strategies encourage teachers to engage in teamwork, share knowledge, solve instructional problems collectively, and participate in continuous professional development. The study also identifies several supporting factors, including teacher commitment, mutual trust, leadership competence, and institutional support, while challenges such as limited time, resistance to change, and technological constraints may hinder collaborative efforts. Overall, the results indicate that effective principal leadership management contributes substantially to the development of a positive collaborative culture, which in turn enhances teacher professionalism, instructional quality, and school effectiveness. The study concludes that sustainable collaborative culture requires strong leadership commitment, continuous support, and active participation from all members of the school community.